2015
DOI: 10.3122/jabfm.2015.02.140273
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Portable Sleep Monitors to Detect Obstructive Sleep Apnea (OSA) in a Vulnerable Urban Population

Abstract: Purpose Portable sleep monitors may offer a convenient method to expand detection of obstructive sleep apnea (OSA), yet few studies have evaluated this technology in vulnerable populations. We therefore aimed to assess the feasibility and acceptability of portable sleep monitors for detection of OSA in a prediabetic, urban minority population. Methods We recruited a convenience sample of participants at their 12-month follow-up for a community-partnered, peer-led lifestyle intervention aimed to prevent diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Many were based on oximetry data alone, which is inferior to PSG or even portable monitors. 36,37 The portable monitoring task force of AASM guidelines clearly states that portable monitors, at minimum, must record airflow, respiratory effort, and blood oxygenation, and hence, use of oximetry data alone for interpretation is no longer considered appropriate. 38 However, our research has a few limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Many were based on oximetry data alone, which is inferior to PSG or even portable monitors. 36,37 The portable monitoring task force of AASM guidelines clearly states that portable monitors, at minimum, must record airflow, respiratory effort, and blood oxygenation, and hence, use of oximetry data alone for interpretation is no longer considered appropriate. 38 However, our research has a few limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies were based on oximetry alone, which is inferior to PSG or even portable monitors. [68,69] There are several limitations of this study as well. First, compliance to CPAP treatment is too low and could be randomized in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, see the articles on interprofessional care, 1-5 continuity, 6 cultural competence, 7 continuing competence, 8,9 and provision of essential care to the underserved. 10 We provide additional insight into how different physicians interpret similar data on older patients. 11 We have broad physician input into potential items to be considered in the national Choosing Wisely campaign, with many excellent interventions identified that should be performed less often.…”
mentioning
confidence: 99%
“…Nickerson et al 10 looked at the feasibility of using portable sleep monitors in a particularly needy population, that is, those from a community health center who were nonwhite, at high risk for many health morbidities, and with many uninsured. Notably, all the patients returned the monitors, and approximately two thirds were eventually formally diagnosed with sleep apnea.…”
mentioning
confidence: 99%